2017
DOI: 10.18761/perspectivas.v5i2.129
|View full text |Cite
|
Sign up to set email alerts
|

Considerações experimentais sobre os efeitos do controle por rejeição na formação de classes de equivalência

Abstract: Experimentos que investigam questões relacionadas à ocorrência de resultados negativos em testes de formação de classes de equivalência referem-se frequentemente ao estabelecimento do controle por rejeição (i.e., relação modelo/S-). Com base nas análises teóricas e empíricas descritas nos estudos seminais, argumentou-se que o estabelecimento de tais relações daria origem a padrões de respostas que seriam opostos àqueles geralmente descritos em testes de reflexividade e transitividade. No entanto, a maioria dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Previous studies have shown that establishing reject control in two‐choice MTS required biasing procedures in conjunction with other procedural modifications (e.g., Huziwara et al, 2014; Johnson & Sidman, 1993; Perez, Tomanari, & Vaidya, 2015; Perez et al, 2019; Perez et al, 2020). To establish select control during baseline training in the present study, only different proportions of S + and S − were sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that establishing reject control in two‐choice MTS required biasing procedures in conjunction with other procedural modifications (e.g., Huziwara et al, 2014; Johnson & Sidman, 1993; Perez, Tomanari, & Vaidya, 2015; Perez et al, 2019; Perez et al, 2020). To establish select control during baseline training in the present study, only different proportions of S + and S − were sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…There are a small number of studies that have used the biasing procedure just described to attempt to establish reject control and test for the emergent relations predicted by Carrigan and Sidman's (1992) theoretical analysis, and the results have shown that this procedure alone can be insufficient in producing the predicted classes (e.g., Huziwara et al, 2014; Perez et al, 2019). When additional procedures were implemented during baseline conditional discrimination training, however, performances indicating the presence of reject control were observed (e.g., Johnson & Sidman, 1993; Perez, Tomanari, & Vaidya, 2015; Perez et al, 2019; Perez et al, 2020).…”
mentioning
confidence: 99%
“…A Figura 2 mostra que oito artigos experimentais (53,3%) se enquadraram na categoria "Equivalência de Estímulos" (Huziwara et al, 2014;Dalto & Haydu, 2015 Barban & Leonardi, 2018), um (6,7%) na "Esquemas de Reforçamento" (Costa et al, 2014) e um (6,7%) na categoria "Resolução de Problemas" (Filho et al, 2016).…”
Section: Qual(is) Foi(ram) O(s) Tema(s) Da(s) Pesquisa(s) Experimentaunclassified